Osteogenesis Imperfecta - Zafar, Muhammad; Nazir, Anisa Fatima (Journal of Postgraduate Medical Institute, 2011)
Osteogenesis Imperfecta also known as Maladie de Lobstein is a group of inheritable, generalized disorders of connective tissue with clinical manifestations in the skeleton, eyes, joints, ligaments, teeth, sclerae and skin. Biochemical studies suggest that the defect involves collagen material. The frequency of O.I. has been estimated at more than one in twenty births.